Polychaete species infected pearl oyster Pinctada maxima at Padang Cermin Water, Lampung - Y. Hadiroseyani; D. Djokosetiyanto; . Iswadi (Jurnal Akuakultur Indonesia)
This study was conducted to determine polychaetes infecting pearl oyster Pinctada maxima reared at Padang Cermin Bay, Lampung.  There were 9 genera of polychaetes harboured on the shell of pearl oysters from Teluk Padang Cermin Lampung.  Those are Eunice, Lysidice, Nereis, Phylodoce, Polycirrus, Polydora  Salmacing,  Streblosoma and Syllis which attached on external surface of the shell and some of them were burrowed into the shell.